Application of optical coherence tomography in cardiovascular diseases: bibliometric and meta-analysis - Lian, Wenjing; Chen, Cong; Wang, Jie; Li, Jun; Liu, Chao; Zhu, Xueying (Frontiers in Cardiovascular Medicine, 2024)
Significance Since the advent of Optical Coherence Tomography (OCT) two decades ago, there has been substantial advancement in our understanding of intravascular biology. Identifying culprit lesion pathology through OCT could precipitate a paradigm shift in the treatment of patients with Acute Coronary Syndrome. Given the technical prowess of OCT in the realm of cardiology, bibliometric analysis can reveal trends and research focal points in the application of OCT for cardiovascular diseases. Concurrently, meta-analyses provide a more comprehensive evidentiary base, supporting the clinical efficacy of OCT-guided Percutaneous Coronary Intervention (PCI). Design This study employs a dual approach of Bibliometric and Meta-analysis. Methods Relevant literature from 2003 to 2023 was extracted from the Web of Science Core Collection (WoSCC) and analyzed using VOSviewer, CiteSpace, and R for publication patterns, countries, institutions, authors, and research hotspots. The study compares OCT-guided and coronary angiography-guided PCI in treating adult coronary artery disease through randomized controlled trials (RCTs) and observational studies. The study has been reported in the line with PRISMA and AMSTAR Guidelines. Results Adhering to inclusion and exclusion criteria, 310 publications were incorporated, demonstrating a continual rise in annual output. Chinese researchers contributed the most studies, while American research wielded greater influence. Analysis of trends indicated that research on OCT and angiography-guided PCI has become a focal topic in recent cohort studies and RCTs. In 11 RCTs (n = 5,277), OCT-guided PCI was not significantly associated with a reduction in the risk of Major Adverse Cardiac Events (MACE) (Odds ratio 0.84, 95% CI 0.65–1.10), cardiac death (0.61, 0.36–1.02), all-cause death (0.7, 0.49–1.02), myocardial infarction (MI) (0.88, 0.69–1.13), target lesion revascularization (TLR) (0.94, 0.7–1.27), target vessel revascularization (TVR) (1.04, 0.76–1.43), or stent thrombosis (0.72, 0.38–1.38). However, in 7 observational studies (n = 4,514), OCT-guided PCI was associated with a reduced risk of MACE (0.66, 0.48–0.91) and TLR (0.39, 0.22–0.68). Conclusion Our comprehensive review of OCT in cardiovascular disease literature from 2004 to 2023, encompassing country and institutional origins, authors, and publishing journals, suggests that OCT-guided PCI does not demonstrate significant clinical benefits in RCTs. Nevertheless, pooled results from observational studies indicate a reduction in MACE and TLR.